Надійність пагонових систем тропічних орхідних (Epidendroideae: Orchidaceae Juss.) - Cherevchenko, T.M.; Buyun, L.I.; Kovalska, L.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
On the examples of different orchid species of Epidendroideae subfamily Orchidaceae family, representing both a great diversity of shoot types formation and the structure of separate shoots, an effort to demonstrate the patterns of functioning of shoot systems of tropical orchids as a modular or metameric construction from view point of plant system reliability theory has been undertaken.